Management of Post-traumatic Dental Immature Teeth at the Growing Phase - Fitriani, Yufita; Juniar, Eriza (Journal of Syiah Kuala Dentistry Society, 2023)
Background: Anterior dental trauma is common in children. Traumatic dental injury in children's teeth can interfere with the function of speech, mastication, aesthetics, eruption of permanent teeth, and the growth and development of teeth and jaws. An unclosed and wide-open apex (immature tooth) is a complex case for a pediatric dentist due to multiple stages of treatment and different options compared to adults. Objective: To explain the management of post-traumatic dental immature teeth. Case: An eight-year-old male child came to the clinic one month after getting a dental injury. This case is classified into Class IV Ellis and Davey's traumatic dental injury classification with immature teeth. Case Management Apexification uses Ca(OH)2 paste followed by an acrylic provisoris restoration while the jaw grows. Conclusion: Apexification using Ca(OH)2 paste followed by acrylic provisions crown restoration is a proper treatment in this case.